Characterization of Seed Rot Resistance to Pythium aphanidermatum in Soybean. Issue 3 (16th June 2017) - Urrea, Keiddy; Rupe, John; Chen, Pengyin; Rothrock, Craig S.
Abstract : The soybean [ Glycine max (L.) Moench.] cultivar 'Archer' has a single gene for resistance to hypocotyl infection by Pythium aphanidermatum ( Rpa1 ) but it is not known if this source of resistance limits pre‐emergence damping‐off caused by this pathogen. Resistance in Archer to pre‐emergence damping‐off caused by P. aphanidermatum was characterized in 84 F2:6 soybean lines derived from a cross of 'Archer' (the resistant parent) and 'Hutcheson' (the susceptible parent). The lines and parents were evaluated for percent germination at 7 days and percent stand at 14 days via a seed plate assay and an infested vermiculite assay, respectively. The lines were assayed with 5403 single‐nucleotide polymorphism (SNP) markers and the results compared with the assay data. Seed germination and plant stands for the Archer × Hutcheson population fit the model for a quantitative trait indicating that Pythium resistance was controlled by multiple genes or quantitative trait loci (QTLs). Two QTLs were identified by each of the two phenotyping methods on chromosomes 4 and 7. The QTL on chromosome 4 explained 8.29 and 13.76 % of the variation and the QTL on chromosome 7 accounted for 4.5 and 13.85 % of the variation in the seed plate and infested vermiculite assays, respectively. Heritability of resistance was 0.8534 and 0.6955 in the seed plate and the infested vermiculite assays, respectively, indicating that Pythium resistance from Archer could successfully be incorporated into soybean breeding programs. These QTLs were not associated with Rpa1, the gene for resistance to hypocotyl symptoms.